Lipid trajectories improve risk models for Alzheimer’s disease and mild cognitive impairment - Bruce A. Chase; Roberta Frigerio; Chad J. Yucus; Smita Patel; Demetrius Maraganore; Alan R. Sanders; Jubao Duan; Katerina Markopoulou (Journal of Lipid Research)
In this retrospective, case-control study, we tested the hypothesis that blood-lipid concentrations during the decade prior to cognitive symptom onset can inform risk prediction for Alzheimer's disease (AD) and stable mild cognitive impairment (MCI). Clinically well-characterized cases were diagnosed using Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria; MCI cases had been stable for ≥5 years; and controls were propensity matched to cases at symptom onset (MCI: 116 cases, 435 controls; AD: 215 cases, 483 controls). Participants were grouped based on (i) longitudinal trajectories and (ii) quintile of variability independent of the mean (VIM) for total cholesterol, HDL-C, low-density lipoprotein cholesterol, non-HDL-C, and ln(triglycerides). Risk models evaluated the contributions of lipid trajectory and VIM groups relative to APOE genotype or polygenic risk scores (PRSs) for AD and lipid levels and major lipoprotein confounders: age, lipid-lowering medications, comorbidities, and other longitudinal correlates of blood-lipid concentrations. In models with AD-PRS, higher MCI-risk was associated with the two lower HDL-C trajectories [odds ratios: 3.8(1.3−11.3; P = 0.014), 3.2(1.1−9.3; P = 0.038), relative to the high trajectory], and the lowest VIM quintile of non-HDL-C [odds ratio: 2.2 (1.3−3.8: P = 0.004), relative to quintiles 2−5]. Higher AD-risk was associated with the two lower HDL-C trajectories [odds ratios: 2.8(1.5−5.1; P = 0.001), 3.7 (2.0−7.0; P < 0.001)], and the lowest VIM quintile of total cholesterol [odds ratio: 2.5(1.5−4.0: P < 0.001)]. Inclusion of lipid-trajectory and VIM groups improved risk-model predictive performance independent of APOE and AD or lipid-level PRSs, providing important real-world perspectives on how longitudinal levels and variation of blood-lipid concentrations contribute to risk of cognitive decline.